Larvicidal activity of extracts from Ammi visnaga Linn. (Apiaceae) seeds against Culex quinquefasciatus Say. (Diptera: Culicidae) - Pavela, Roman; Vrchotová, Naděžda; Tříska, Jan (Experimental parasitology, 2016)
Efficacies of the Ammi visnaga seeds extract and a majority of substances on larval Culex quinquefasciatus mortality in various development stages including pupae were studied. The effect of exposure time on larval mortality was also studied. The effect of sublethal concentrations or short exposure times on further larval development and subsequent fecundity in adults were studied as well. Lethal doses of the extract were estimated for the 2nd, 3rd and 4th instar of C. quinquefasciatus (LC50 for 18, 23 and 180 mg L(-1), respectively). The majority of furanochromenes, khellin and visnagin, were identified by analysing the extract. Khellin was significantly more effective compared to visnagin, whose LC50 was estimated at 8, 10 and 41 mg L(-1) for the 2nd, 3rd and 4th instar larvae. Khellin showed very fast efficacy on mortality for the 3rd instar larvae in a concentration of 100 mg L(-1). Fifty percent mortality was determined 30 min after application, a time which was considerably shorter compared to the extract (113 min) or visnagin (169 min). The effect of the application of lethal concentrations on C. quinquefasciatus larval mortality was studied. The least number of adults were hatched after application of the extract and khellin (41.8% and 37.9%, respectively), less than after visnagin application (46.7%) or in the control (94.2%). LC50 application caused lower fecundity in the hatched adults, lower hatchability of the eggs, and also very low natality, more than 77% lower for khellin compared to the control. A short exposure, corresponding to our estimated LT30, caused no significant acute toxicity in the larvae (until 24 h) for the extract or visnagin (4.3% and 11.5%, respectively); however, 18 min of action from khellin caused a 54.3% mortality rate of the larvae within 24 h.
Keywords: Chromatography, High Pressure Liquid; Plant Extracts; Furanochromenes; Botanical larvicide; Khellin; LD50; larva; insekticidy; Female; zvířata; rostlinné extrakty; Culex; Insecticides; Ammi; časové faktory; Seeds; ženské pohlaví; Male; Mosquito; Sublethal effect; Lethal Dose 50; Visnagin; Larva; Animals; mužské pohlaví; Time Factors; vysokoúčinná kapalinová chromatografie; khelin; semena rostlinná